2018
DOI: 10.1136/bmjopen-2017-019367
|View full text |Cite|
|
Sign up to set email alerts
|

Role of the family doctor in the management of adults with obesity: a scoping review

Abstract: ObjectivesObesity management is an important issue for the international primary care community. This scoping review examines the literature describing the role of the family doctor in managing adults with obesity. The methods were prospectively published and followed Joanna Briggs Institute methodology.SettingPrimary care. Adult patients.Included papersPeer-reviewed and grey literature with the keywords obesity, primary care and family doctors. All literature published up to September 2015. 3294 non-duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 183 publications
0
18
0
Order By: Relevance
“…The results are to be incorporated in clinical pathways for primary care teams. A scoping review published by Sturgiss in 2018 showed that the literature is divided on the role family doctors and other health professionals should play in obesity management. Although general practitioners are mostly involved in diagnosis and assessment, their role in obesity care is often underestimated .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are to be incorporated in clinical pathways for primary care teams. A scoping review published by Sturgiss in 2018 showed that the literature is divided on the role family doctors and other health professionals should play in obesity management. Although general practitioners are mostly involved in diagnosis and assessment, their role in obesity care is often underestimated .…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review published by Sturgiss in 2018 showed that the literature is divided on the role family doctors and other health professionals should play in obesity management. Although general practitioners are mostly involved in diagnosis and assessment, their role in obesity care is often underestimated . Another review concluded that studies performed in primary care provide little evidence on the effectiveness of overweight and obesity management and that further research is needed to define the role of primary care providers in the context of comprehensive and multi‐professional care .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to identify current barriers to the weight management of patients in primary care in order to improve their treatment. According to a recent review of obesity management in primary care, Germany has not conducted many surveys on managing obesity, as compared to other countries, in particular the USA [9]. Consistent findings have been reported with regard to stigmatizing attitudes in health care [10].…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, patients viewed the physiotherapists' role in knee OA management as being situated within a GP-led healthcare team. GPs are often the first point of contact for people with musculoskeletal disease; however, data from Australia show that GPs give advice regarding weight loss in only 15% of knee OA patients (Brand et al, 2014), consistent with the low levels of obesity advice given by physicians internationally (Sturgiss, Elmitt, Haelser, van Weel, & Douglas, 2018). By contrast, GP referral to other health practitioners is the most frequent mode of nonpharmacological management (Brand et al, 2014).…”
Section: Discussionmentioning
confidence: 97%